Albulayomterc impact exercises to develop explosive power level and motor nerve stimulation and motor unit area of effective lower limb muscles - Kadhim, Mohammed; Altay, Usama (Journal of Physical Education, 2007)
The study aimed to prepare a training program by using plyometric style to develop the explosive power of lower limbs muscles and knowing the effect of using this program in developing the explosive power and the level of neural stimulation and the area of effective motor unit for the lower limbs muscles. The researchers hypothesis a significant differences between the pre and post test for the both groups (control and experimental), so there is a significant differences in the post test between the two groups (control and experimental) in the variable of study. The researchers used the experimental method, and the subject were (16) players from physical education team/University of Baghdad, which divided in to two groups (control and experimental) each one consist of (8) players. The researchers used standing vertical jump test to measure the explosive power and the electromyography (EMG) to measure the level of neural stimulation and the area of effective motor unit for the lower limbs muscles. The researchers concluded the effective of using plyometric exercises in developing the explosive power and the intensity of the level of neural stimulation and the area of effective motor unit for the lower limbs muscles, and the increase of neural stimulation and the area of motor unit have a significant effect on the power out put. The researchers recommended using plyometric exercises for developing the explosive power for the lower limbs muscles and to use (EMG) to identify the benefit of plyometric exercises